AMP-activated protein kinase regulates alternative pre-mRNA splicing by phosphorylation of SRSF1. Issue 12 (24th June 2020) - Matsumoto, Eri; Akiyama, Kaho; Saito, Takuya; Matsumoto, Yu; Kobayashi, Ken-Ichi; Inoue, Jun; Yamamoto, Yuji; Suzuki, Tsukasa
Abstract : AMP-activated protein kinase (AMPK) regulates cellular energy homeostasis by inhibiting anabolic processes and activating catabolic processes. Recent studies have demonstrated that metformin, which is an AMPK activator, modifies alternative precursor mRNA (pre-mRNA) splicing. However, no direct substrate of AMPK for alternative pre-mRNA splicing has been reported. In the present study, we identified the splicing factor serine/arginine-rich splicing factor 1 (SRSF1) as a novel AMPK substrate. AMPK directly phosphorylated SRSF1 at Ser133 in an RNA recognition motif. Ser133 phosphorylation suppressed the interaction between SRSF1 and specific RNA sequences without altering the subcellular localization of SRSF1. Moreover, AMPK regulated the SRSF1-mediated alternative pre-mRNA splicing of Ron, which is a macrophage-stimulating protein receptor, by suppressing its interaction with exon 12 of Ron pre-mRNA. The findings of this study revealed that the AMPK-dependent phosphorylation of SRSF1 at Ser133 inhibited the ability of SRSF1 to bind RNA and regulated alternative pre-mRNA splicing.